Histopathological spectrum of cervical biopsies – a 5 year retrospective study - Dr Kanya Kumari; Dr Umarani M K; Dr Bharathi M (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: cervix is a gateway to numerous non neoplastic and neoplastic gynecological lesions. Cervical cancer is the leading cancer in Indian women and second most common cancer in women worldwide next to breast cancer.Objectives: 1) To study the histopathological features of cervical lesions. 2) To study the age distribution and relative frequency of various cervical lesions.Materials and Methods: This is 5 years retrospective study of all cervical biopsies received from 2011-2015 in the department of pathology.Result: In a total of 739 cases studied 365(49.39%) cases were non neoplastic, 113(15.29%) were pre invasive and 261(35.31%) cases were malignant. Cervicitis was the most common non neoplastic lesion and squamous cell carcinoma was the most common cancer.Conclusion: Adequate cervical screening procedure with follow up cervical biopsies helps in early diagnosis and management of premalignant and malignant lesions.